(3cJGH GdabQ hGdRgOs - (3eMeO Hf MHGf Hf CMeO Hf MHGf Hf eYGP Hf eYHO GdJejej, CHh MGJe GdHSJj, hjbGd dg GHf MHGf,J (B354 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi JSHjM dg GdQeGd aEf GdOfjG YdhI ddg JYGdi HZQhQgG s
(3BNQgG (B:s
(3hLYd eaJGMg MH GdOfjG hLYd GdNjQ cdg hLYd eaJGMg GdRgO ajgG agPG eG CQOfG Cfi fPcQg hGdMeO ddg Mb MeOg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B78 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B173s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdMOjK h GdeUWdMs